Response of some wheat cultivars to plot orientation and foliar boron levels - Mohammed, Lana Dhahir; Amin, Sami Mohammad Amin Mohammed (Kurdistan Journal of Applied Research, 2019)
This investigation was conducted to understand the response of three newly introduced bread wheat cultivars to Erbil area (V1: FLORKWA, V2: BAJ and V3: FRANKOLIN) to three boron levels sprayed at elongation stage 0, 1 and 1.5 ppm concentration and oriented (South-North and East-West) row directions to study the vegetative and reproductive growth characters of wheat. The results showed that Leaf area, LAI, weight of leaf, light extinction coefficient, flag leaf length, fertility, number of spike and harvest index significantly increased in EW (East-West) compared to SN (South-North) row direction. While, the spike weight, spike length, number of kernels, grain yield and biological yield significantly increased in SN compare to EW row direction. There were not significant differences observed among different level of boron alone and different cultivars in all studied traits except plant height and 1000 kernels weight of V2 increased compared to other cultivars. Interactions of EW direction with both cultivars and levels of boron factors were improved the vegetable characteristics compared to NS direction. Grain yield of interaction between 1.5 ppm × SN, all cultivars × SN and 1.5 ppm boron × V1 × SN row direction were significantly (P<0.05) increased compared to other interactions. While the harvest index increased in interaction between 0 and 1.5 ppm × EW, V2×EW and 1.5 ppm × V1 × EW compared to other interactions.